Il “palazzo per un viniziano”. Villa la Luna a San Domenico di Fiesole e gli inizi di Giuliano da Sangallo - Rinaldi, Alessandro (Opus Incertum, 2019)
“Fece il medesimo (Giuliano da Sangallo) per un viniziano fuor de la porta a Pinti in Camerata, un palazzo”. The building Vasari refers to is villa La Luna, later known as Guadagni, in San Domenico near Fiesole. The “viniziano” is Girolamo Guadagni, member of a rich merchant family residing in Florence since about 1450. The villa was already completed in 1475, when it was mentioned in Girolamo’s will and thus should be included among the early works of the professional career of Giuliano da Sangallo. The building develops several themes already present in modern villa architecture such as the U plan and the visible base level, which can be found at the Medici villa and the Badia Fiesolana and which offer a strict geometric interpretation enhanced with all’antica references such as the double divergent stairs leading underground. The formal asset that is reached here – although somehow mitigated by traditional elements – will find new and more radical developments at the villa of Poggio a Caiano.